The Development and Applications of Zirconia in Modern Dentistry - Khaled El-gergeni,; Aya Saeh,; Hanan Iirhohuma,; Mabroukah Dakheel, (AlQalam Journal of Medical and Applied Sciences, 2025)
Zirconia, a remarkable material in modern dentistry, has transformed restorative and implant procedures due to its exceptional mechanical properties, aesthetic versatility, and biocompatibility. This paper delves into the evolution of zirconia, exploring its fundamental properties, advanced manufacturing techniques, and diverse applications in both restorative dentistry and implantology. We also address the current challenges and limitations associated with its clinical use, while highlighting promising future directions and innovations in the ﬁeld. The increasing adoption of zirconia, particularly in full-contour restorations and dental implants, signifies a major leap forward in dental materials science, offering patients durable, aesthetically pleasing, and biocompatible solutions for a wide range of dental needs.